Microclimate Impacts of Land Cover Types in Halu Oleo University Botanical Garden and Its Surroundings - Kandari, Aminuddin Mane; Marwah, Sitti; Kasim, Safril; Indriyani, Lies; Albasri; Agus Salim Mando, La Ode; Nurdin, Arianto; Syamsuddin; Munadi, La Ode Muhamad; Fahyuddin (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Halu Oleo University (UHO) Botanical Garden is one of the green open spaces that contribute to maintaining climate stability and environmental comfort in Kendari City, along with the high land use change due to increased population and city progress. The study aimed to determine the effect of land cover types on microclimate in UHO Botanical Garden and its surroundings. The research was conducted from June 2021 to January 2022. The research was conducted on three types of vegetation land cover. The variables measured were microclimate, including light intensity, temperature, relative humidity, and temperature humidity index. Measurements were conducted in the morning, afternoon, and evening. The method used was descriptive quantitative and statistical analysis using the analysis of variance and the least significant difference (LSD) test. The results showed that the microclimatic conditions of UHO Botanical Garden in tree-dominant land cover are more comfortable and significantly different from grass-dominant and settlement-dominant, but they are not significantly different between grass-dominant and settlement-dominant. This fact indicates the importance of the conservation of tree vegetation and the need for supervision so that there is no diversion of functions into settlements to maintain the preservation and sustainability of UHO Botanical Garden as one of the green open spaces that control climate stability and environmental comfort in Kendari City. Keywords: botanical garden, microclimate, settlement, temperature humidity index, vegetation